"XiaoLingTong" : a miracle for UTStarcom a disruptive tech in China? - Sanderson, Jihong W. (London : SAGE Publications Ltd, 2017)
Within the space of only two or three years, a new wireless telecommunications technology called XiaoLingTong (XLT), introduced to China by UTStarcom, became the main driver for revenue growth for the fixed line carriers. With billions of dollars in annual income at stake, the mobile phone network operators attacked XLT, calling it as an obsolete technology and a wasteful infrastructure investment, a sentiment echoed frequently in the Chinese media. Aside from the question of where XLT fits into the telecommunications industry, the fact is, it did contribute dramatically to China Telecoms growth and brought UTStarcom prestige, profits, and an amazing 60 to 70% market share in China. But what is the future of XiaoLingTong?
Originally published: Sanderson, J. W. (2004). "XiaoLingTong": A miracle for UTStarcoma disruptive tech in China? The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; UTStarcom; New products -- China; Product management -- China; Telecommunication -- China